The mediating role of metabolic syndrome in cardiovascular diseases - Noryanti, Muhammad; Sajid, Mirza Rizwan; Roslinazairimah, Zakaria; Ahmad, Shahbaz (AIP Publishing, 2019)
Cardiovascular diseases (CVDs) are a group of heart diseases which is globally considered as a leading cause of mortality and an ultimately huge burden to the economies. In this paper, we propose a new role of the metabolic syndrome (MS) as a mediator of the relationship of CVDs and its socio-demographic risk factors. Mediation is a phenomenon which looks simple but methodologically it needs a realistic attention of researchers to investigate the true influence of cause on effect to the variables by splitting its effect into direct and indirect paths. Past studies have mainly investigated the direct paths of social-demographic risk factors between MS and CVDs. In this paper, we discuss direct relationships and uncover the indirect relationship between CVDs and the risk factors. Then, we developed theoretically the mediator role of MS in the relationship of socio-demographic risk factors and CVDs. A comprehensive relationship-based model of social-demographic risk factors, MS and CVDs has been proposed for the future researches. It would help in more precise risk estimation of CVDs and ultimately delay in the onset of fatal CVDs events.